2023
DOI: 10.11591/ijai.v12.i1.pp415-421
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of machine learning models for breast cancer diagnosis

Abstract: <p><span lang="EN-US">Breast cancer is the most common cause of death among women worldwide. Breast cancer can be detected early, and the death rate can be reduced. Machine learning techniques are a hot topic for study and have proved influential in cancer prediction and early diagnosis. This study's objective is to predict and diagnose breast cancer using machine learning models and evaluate the most effective based on six criteria: specificity, sensitivity, precision, accuracy, F1-score and recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…gini, max_depth: none, n_estimators: 150 Effectively addressing class imbalance through techniques such as weighted classes AdaBoost [? ], [120] n_estimators: 50, learning_rate: 0.5, algorithm: SAMME Addressing the issue of class imbalance by assigning greater weight to prediction errors on samples from the positive class XGBoost [113], [115], [120], [128], [196], [197] n_estimators: 300, scale_pos_weight: 1, max_depth: 4, Sampling method: uniform, eta: 0.3, booster: gbtree Provides numerous parameters that can be optimized Bagging [125] n_estimators: 20, base_estimator: decision tree Becoming more robust to outliers SVM [7], [40], [108], [120], [160], [172] Kernel: rbf, gamma: 1, C: 10 Effective in high-dimensional feature space KNN [76], [108], [120], [124], [145], [199] Algorithm: ball_tree, p:2, n_neighbors: 14 Capturing non-linear and complex patterns in data MLP [115] Optimizer: Adam, learning rate: 0.001 Identifying complex patterns that may be associated with cancer CNN [96] Learning rate: 0.01, Epochs: 100, Optimizer: Adam…”
Section: Flexible In Tuning Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…gini, max_depth: none, n_estimators: 150 Effectively addressing class imbalance through techniques such as weighted classes AdaBoost [? ], [120] n_estimators: 50, learning_rate: 0.5, algorithm: SAMME Addressing the issue of class imbalance by assigning greater weight to prediction errors on samples from the positive class XGBoost [113], [115], [120], [128], [196], [197] n_estimators: 300, scale_pos_weight: 1, max_depth: 4, Sampling method: uniform, eta: 0.3, booster: gbtree Provides numerous parameters that can be optimized Bagging [125] n_estimators: 20, base_estimator: decision tree Becoming more robust to outliers SVM [7], [40], [108], [120], [160], [172] Kernel: rbf, gamma: 1, C: 10 Effective in high-dimensional feature space KNN [76], [108], [120], [124], [145], [199] Algorithm: ball_tree, p:2, n_neighbors: 14 Capturing non-linear and complex patterns in data MLP [115] Optimizer: Adam, learning rate: 0.001 Identifying complex patterns that may be associated with cancer CNN [96] Learning rate: 0.01, Epochs: 100, Optimizer: Adam…”
Section: Flexible In Tuning Parametersmentioning
confidence: 99%
“…Machine learning can be used for data mining in the healthcare sector [4]. Applying machine learning in health data can help predict if a patient might have six chronic diseases: diabetes mellitus [5], [6]; cancer [7], [8]; stroke [9], [10]; hypertension [11], [12]; kidney failure [13], [14]; and heart issues [15], [16].…”
Section: Introductionmentioning
confidence: 99%
“…ML models have demonstrated their contribution to the prediction and early diagnosis of cancer. For example, in [27] they conducted a study to predict and diagnose breast cancer using ML models, for which they used parameters such as specificity, sensitivity, precision, accuracy, precision, and F1 score. The GBDT model obtained a score of 96.77 outperforming all other models.…”
Section: Previous Studiesmentioning
confidence: 99%
“…AI systems have shown significant progress in the domain of image identification, which plays a crucial role in the diagnosis and detection of illnesses. Recent studies have shown that AI-assisted imaging systems have exhibited comparable diagnostic performance to that of human medical professionals in some medical conditions [3,4]. SARS-CoV-2, an emerging coronavirus responsible for the onset of COVID-19 disease in human beings, first manifested in Wuhan, China, in December 2019 [5].…”
Section: Introductionmentioning
confidence: 99%